Rehabilitation of the Human Bone-Muscle System - Olaru, Adrian (IntechOpen, 2022)
Mechatronic systems, especially exoskeletons, are a potential solution for physical rehabilitation in people with neurological problems or physical disabilities. This book discusses the relationship between bio-signals (EMG) and kinematic parameters (articular angles) in developing an assistance exoskeleton. A variety of constitutive materials and design principles are described and discussed, as are strategies for designing vacuum-powered actuators. The book also examines the main materials and fabrication processes used for developing exoskeletons and highlights the most promising approaches.